The Effect of Aromatherapy on Sleep Quality in the Elderly at Rindang Asih I Nursing Home in Semarang - Addini, Ragil Aidil Fitriasari; Sutejo, Mianti Nurrizky; Bhagaskara, Dewa Rahma; Dhikta, Yessa Kristia (Journal of Health Science and Medical Therapy, 2023)
Sleep disorders or insomnia is one of the disorders that frequently occurs in the elderly. The treatment that can be given for sleep disorders that occur in the elderly is aromatherapy. Aromatherapy is a treatment technique using the aroma of essential oils resulting from the distillation process of various parts of plants, flowers and trees that contain therapeutic properties. Aromatherapy can provide stimulation to the olfactory cortex which stimulates the brain and impulses reach the limbic system, thereby affecting mood. This research is a quasi-experimental study with a pre-posttest design. The population in this study were all elderly people in the Rindang Asih I Nursing Home in Semarang. The results of the Friedman effect test in this study with a p-value = 0.000. The administration of aromatherapy had an effect on the sleep quality of the elderly in the Rindang Asih I Nursing Home in Semarang.